Modulação da inflamação no tecido adiposo marrom: o papel do exercício físico crônico na infiltração e polarização de macrófagos - Preto, Isabela Aparecida Dosualdo [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
In inflammatory context, currently associated with obesity and insulin resistance, there is a growing interest in the role of macrophages, since they accumulate in adipose tissue in obese above and also for presenting relation with insulin resistance parameters. Macrophages can present two types of activation, a pro-inflammatory known as M1 or classical, characterized by the predominance of inflammatory cytokines (TNF and iNOS) and associated with insulin resistance; and another antiinflammatory or alternatively named M2 where there is a predominance of antiinflammatory substances (IL-10 and arginase-I) and related improvement in insulin sensitivity. Meanwhile, increasingly evident it becomes the exercise can be a useful therapy for the treatment of insulin resistance due to obesity, since it exhibits antiinflammatory effect and is capable of promoting increased signaling and sensitivity insulin. Recent evidence demonstrated beneficial effect of physical exercise (acute and chronic) in the polarization of the white adipose tissue macrophages in obese rodents. However, it remains unclear the effect of high fat diet and exercise in infiltration and macrophage polarization in brown adipose tissue. Thus, in this project, we investigated the effect of high fat diet and chronic exercise on infiltration and macrophage polarization in brown adipose tissue. rats were used Wistar that when they reach 6 weeks of age were divided into the following groups: control animals fed a standard diet (CTL), obese animals fed high fat diet sedentary (DH) and exercised (DH+EC). The groups have infiltration and macrophage polarization evaluated over 8 weeks. The exercises consist in swimming for 1 hour per day, five days per week for 8 weeks, supporting a load that is increased gradually ... (Complete abstract electronic access below)

No contexto inflamatório, atualmente associado com a obesidade e resistência à insulina, há um crescente interesse sobre o papel dos macrófagos, visto que estes se acumulam no tecido adiposo branco num quadro de obesidade e também por apresentarem relação com os parâmetros de resistência à insulina. Os macrófagos podem apresentar dois tipos de ativação, uma pro-inflamatória conhecida como M1 ou clássica, caracterizada pelo predomínio de citocinas inflamatórias (TNFassociada à resistência à insulina; e outra anti-inflamatória denominada M2 ou alternativa onde há o predomínio de substâncias anti-inflamatórias (IL-10 e arginase-I) e relação com melhora na sensibilidade à insulina. Paralelamente, torna-se cada vez mais evidente que o exercício físico pode ser uma terapia útil para o tratamento da resistência à insulina em decorrência da obesidade, uma vez que apresenta efeito anti-inflamatório e é capaz de promover o aumento da sinalização e da sensibilidade à insulina. Evidencias recentes demonstraram efeito benéfico do exercício físico (agudo e crônico) na polarização de macrófagos do tecido adiposo branco de roedores obesos. Entretanto, permanece ainda incerto o efeito do exercício físico na infiltração e polarização de macrófagos no tecido adiposo marrom. Assim, nesse projeto, foi investigado o efeito da dieta hiperlipídica e do exercício físico crônico sobre a infiltração e a polarização de macrófagos no tecido adiposo marrom. Para tanto, foram utilizados ratos da linhagem Wistar, que ao atingirem 6 semanas de idade foram divididos nos seguintes grupos: animais controle alimentados com dieta padrão para roedores (CTL), animais obesos alimentados com dieta hiperlipídica sedentários (DH) ou exercitados (DH+EC). O protocolo de exercício ... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Medicina esportiva; Macrófagos; Insulina; Resistência à insulina; Tecido adiposo; Exercicios fisicos - Aspectos fisiologicos